Social Solidarity in Times of Hate (Revista Paradigma, 2022)
A few decades ago, most countries incorporated a set of guidelines identified with liberal ideologies, which led to the redesign of the states’ role, reducing their redistributive social function. One of the consequences of this choice is an era of constant inequality growth, in which the richest seize most of the benefits arising from the expansion of trade, services and the technological revolution, according to a model in which the opportunities and gains are not for everyone. Limited intergenerational mobility sharpens the feeling of injustice and feeds social conflicts, paving the way for polarizing discourses, which foster differentiation between included and outsiders and hate. Based on these elements, this research sought to explain the expansion of the enemy's culture and the rise of populist and authoritarian regimes, a growing phenomenon in present days.